Democracy under Threat: Study of the Implementation of the Rights of Indigenous Peoples to the Management of Natural Resources in Riau Province - Marta, Auradian; Agustino, Leo; Jermsittiparsert, Kittisak (Jurnal Politik Indonesia: Indonesian Political Science Review, 2020)
This article discusses why the failure to fulfill indigenous peoples' rights in managing natural resources in Riau Province will pose a threat to democracy. The empirical phenomenon in Riau Province showed that even though regulations in recognition and protection existed, conflicts in forest management and land belonging to indigenous peoples continued to occur. This study uses qualitative research methods by collecting data through interviews and documents. The results show that the non-fulfillment of indigenous peoples' rights in managing natural resources will lead to injustice, discrimination, and economic inequality. It will ultimately have implications for the decline in the quality of democracy and the government regime's legitimacy. The implementation of indigenous peoples' rights in managing natural resources in Riau Province is limited to democratic rhetoric. The conclusion in this study is that violations of indigenous peoples' rights will contribute to democratic de-consolidation.